Synthesized Drug from Medicinal Plant phytochemicals Effectively Targets ECM1 Gene Mutations in Ulcerative Colitis - Munir, Anum; Hu, Lianhai (Letters in Drug Design & Discovery, 2022)
Background: Ulcerative colitis (UC); an inflammatory bowel disease primarily affects the mucosa of the colon. Depending on its mode of appearance, it can affect either the entire colon or even the distal rectum. UC can manifest in both genders and every generation, but most generally appear in people between the ages of 15 and 30. The extracellular matrix protein-1 (ECM1) gene is an important candidate, mutations leading to tissue damage in patients with ECM1 single-nucleotide polymorphisms are likely to intensify tissue damage caused by Metalloproteinase9 resulting in UC. Methods: In this analysis, approval for the synthesis of Chemical Compound was obtained from the scientific committee of the Department of Traditional Chinese Medicine, Qilu Hospital, China. Several derivatives used as UC therapy were selected to build the pharmacophore model, using a ligandbased pharmacophore modeling approach and virtual screenings were done for the identification of suitable drug compounds. The selected compound was then synthesized in-vitro and validated using the molecular docking technique. Results: The synthesized compound fulfills all the characteristics of the non-toxic existence of other drug-likeness laws. The specific interactive amino acids found in the docked complex are arginine (ARG):47, lysine (LYS):54, phenylalanine (PHE):141, aspargine (ASN):51, serine (SER):219, histadine (HIS):144, PHE:214, valine(VAL):220, tyrosine(TYR):145, and TYR:284. The interaction of the synthesized compound with mutated TYR:284 of ECM1 confirmed the viability and safety of a drug molecule as a medication in Ulcerative Colitis care. Conclusion: In the future, its validity can be explored in the laboratory and this synthesized compound can be used as a medication target in clinical studies against TYR:284 mutation in the ECM1 gene.
Keywords: phytochemicals